2023
DOI: 10.3389/fonc.2023.1067735
|View full text |Cite
|
Sign up to set email alerts
|

The progress in our understanding of CIN in breast cancer research

Abstract: Chromosomal instability (CIN) is an important marker of cancer, which is closely related to tumorigenesis, disease progression, treatment efficacy, and patient prognosis. However, due to the limitations of the currently available detection methods, its exact clinical significance remains unknown. Previous studies have demonstrated that 89% of invasive breast cancer cases possess CIN, suggesting that it has potential application in breast cancer diagnosis and treatment. In this review, we describe the two main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Conventional treatment for breast cancer includes surgical resection, radiation therapy, chemotherapy, endocrine therapy, and targeted therapy (Waks and Winer, 2019). Although the prognosis for breast cancer is getting better with the continuous development of medical technology (Fridrichova and Zmetakova, 2019;Guo et al, 2023;Liao and Cao, 2023), recurrence and metastasis remain major challenges because microscopic metastatic lesions may still be present following treatment of the primary lesion and may grow over time, eventually leading to recurrence and metastasis. Furthermore, drug resistance commonly occurs because of the high variability and compensatory adaptation mechanisms of cancer cells, leading to treatment failure (Garcia-Martinez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment for breast cancer includes surgical resection, radiation therapy, chemotherapy, endocrine therapy, and targeted therapy (Waks and Winer, 2019). Although the prognosis for breast cancer is getting better with the continuous development of medical technology (Fridrichova and Zmetakova, 2019;Guo et al, 2023;Liao and Cao, 2023), recurrence and metastasis remain major challenges because microscopic metastatic lesions may still be present following treatment of the primary lesion and may grow over time, eventually leading to recurrence and metastasis. Furthermore, drug resistance commonly occurs because of the high variability and compensatory adaptation mechanisms of cancer cells, leading to treatment failure (Garcia-Martinez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, as per recent data, VPA has significant inhibitory effects on tumor progression in ER-positive BC cell types than others 16 . Interestingly, multiple studies have revealed a higher prevalence of Chromosomal Instability (CIN) in metastatic breast cancer compared to primary breast cancer 25 . This suggests a strong association between CIN and the process of metastasis.…”
Section: Introductionmentioning
confidence: 99%